Research Progress on the Effects of Anthocyanins on Cognitive Function and Their Underlying Mechanisms - Dong, Wen-huan; Wang, Ting; Wang, Zi-ping; Wen, Xin; Huang, Qi-qi; Xiong, Zhang-e (Current Pharmaceutical Biotechnology, 2025)
<span class=
Keywords: anti-inflammatory